If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 3g = -9 + 2g Solving 3g = -9 + 2g Solving for variable 'g'. Move all terms containing g to the left, all other terms to the right. Add '-2g' to each side of the equation. 3g + -2g = -9 + 2g + -2g Combine like terms: 3g + -2g = 1g 1g = -9 + 2g + -2g Combine like terms: 2g + -2g = 0 1g = -9 + 0 1g = -9 Divide each side by '1'. g = -9 Simplifying g = -9
| 3.50=5.25-11 | | 13x+(1-x)(15)=13 | | y=5(x-6)(x+9) | | 10-(8-8n)+8n=-4+12(n+1) | | 5m+m^2= | | 5m+m^2=6m | | 3.50+11=5.25+11 | | 18y+24x= | | 0=-16t^2+144t+0 | | 75x+7=4 | | -15=0.2b | | G(5)=10x-4 | | 29-4(4-x)=1 | | -66=6.6v | | 10z^6+9z^3-9=0 | | 7x-2=5.5 | | 16k^2-52k+30= | | 5x+3y=1500 | | 6x-7=4x+2 | | B-23=33 | | 30.6=5.1k | | 2x-21=x-10 | | 24-3(4-x)=-6 | | 14x-17x=6 | | 6b-4+b=-12 | | 9r-4(r+2)=5(2r-4)-18 | | y=3(x+1)(x-7) | | -13=2.8+a | | 4x^3-3x^2-10x+12=0 | | 2k^2-18k^2d^2= | | Y=-0.7x+4.9 | | 9-18x-15=-52x-126+10 |